1987
DOI: 10.1113/jphysiol.1987.sp016685
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during intermittent cold exposure prevents acclimation to cold rats.

Abstract: SUMMARY1. Energy balance and brown adipose tissue growth were examined in four groups of male Wistar rats: (i) sedentary, living at 24°C (warm), (ii) exercise-trained, 2 h daily, living at 24°C, (iii) living at 24°C but exposed to -5°C, 2 h daily and (iv) living at 24°C but exercise-trained while being exposed to -5°C, 2 h daily.2. Cold exposure during exercise training appeared to have little additional influence on body composition following 28 days of treatment; body mass gain, in addition to protein and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…These findings observed in intermittently cold-acclimated rats have been partially reported by other investigators (LEBLANC 1967;LEBLANC et al, 1967;BARNARD and SKALA, 1970;ARNOLD and RICHARD, 1987) and are among the common adaptations detected in chronically cold-acclimated animals (ALEXANDER, 1979). However, food intake of intermittently CA in the present study was not augmented (Table 1) as observed in other studies (HARRI et al, 1984;ARNOLD and RICHARD, 1987). In chronically cold-exposed animals energy intake is generally increased compensatory to increased energy expenditure (HARRI et al, 1984;RICHARD et al, 1986).…”
Section: Shivering Measurementssupporting
confidence: 83%
See 3 more Smart Citations
“…These findings observed in intermittently cold-acclimated rats have been partially reported by other investigators (LEBLANC 1967;LEBLANC et al, 1967;BARNARD and SKALA, 1970;ARNOLD and RICHARD, 1987) and are among the common adaptations detected in chronically cold-acclimated animals (ALEXANDER, 1979). However, food intake of intermittently CA in the present study was not augmented (Table 1) as observed in other studies (HARRI et al, 1984;ARNOLD and RICHARD, 1987). In chronically cold-exposed animals energy intake is generally increased compensatory to increased energy expenditure (HARRI et al, 1984;RICHARD et al, 1986).…”
Section: Shivering Measurementssupporting
confidence: 83%
“…These observations indicate that our moderate-intensity exercise training program performed with daily, short-term cold exposure did not modify any of the adaptations that were observed to occur in our sedentary, intermittently cold-acclimated rats. Exercise (running) performed simultaneously with intermittent cold exposure has been previously shown to suppress cold acclimation (ARNOLD and RICHARD, 1987). However, in CA-T, T~ decrease measured at -20°C was greater than that in CA-S (Fig.…”
Section: Shivering Measurementsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the body weight of Apodemus sylvaticus and Acomys cahirinus was not affected by cold acclimation (Klaus, Heldmaier, Ricquier, 1988;Khokhlova, Krasnov, Shenbrot, Degen, 2000;Gunduz, 2002); on the contrary, the body weight of Phodopussungorus, Microtusochrogaster, M. pennslvanicus and Clethrionomysglareolus decreased during cold acclimation (Klaus et al, 1988;Wiesinger, Heldmaier, Buchberger, 1989;Voltura, Wunder, 1998;Wang, Wang, 1990). In the study by Arnold, Richard (1987), cold exposure had no additional effect on body composition in physically active rats. Compared to rats trained at 24°C, exercised cold-exposed animals did not utilise more of their fat or protein stores in providing substrate for exercise.…”
Section: Discussionmentioning
confidence: 88%